Politicians as active and participating stakeholders. The case of gender budgeting in Austria. - Korac, Sanja; Moser, Birgit; Rondo-Brovetto, Paolo (Nomos, 2019)
Der Artikel beschäftigt sich mit Politikern als externe Anspruchsgruppe öffentlicher Verwaltungen. Am Beispiel von Gender Budgeting in der österreichischen Bundesverwaltung, wird untersucht, wie Politiker die Einführung einer Geschlechterperspektive in den Budgetprozess beurteilen, und wie sie aktiv an der Arbeit der Verwaltung teilhaben. Die Studie basiert auf Interviews mit Mitgliedern des parlamentarischen Budgetausschusses und einer qualitativen Analyse von Budgetdokumenten. Die Ergebnisse zeigen, dass Politiker die Reaktionsfreudigkeit der Verwaltung auf deren aktive Teilhabe bei der Einführung einer Geschlechterperspektive in den Budgetprozess als eher gering einschätzen.

This article looks at politicians as external stakeholders of the administration. Using the case of gender budgeting at the central government level in Austria, it analyzes the perception of politicians on how (well) gender perspectives have been introduced in the budgetary process, and how these stakeholders have actively participated in the administrations work. The study builds on interviews with members of the parliamentary budget committee and a qualitative analysis of budget documents. The results show that politicians perceive the administration as rather non-responsive to their active participation in introducing gender perspectives in the budgetary process.
Keywords: Haushaltswesen; Geschlecht; Gleichstellung; Gender Budgeting